Who benefits?: the intersection of governance and agency in farmers’ engagement with the Oklahoma Farm to School Program - Thornburg, Gina K. (Kansas State University, 2017)
Farm-to-school (FTS) programs are promoted as direct-marketing opportunities for farmers. As such, they are regarded by advocates and state and federal agencies as a pathway to rural economic development. The implementation of FTS food procurement poses significant challenges, however. Farmers make decisions regarding whether or not to market products to schools after learning about the program and considering an array of signals from multiscalar policies and governance structures. Research to date has left a gap in understanding farmers’ agency as it relates to governance structures and policy signals. This research on farmers’ engagement with the Oklahoma FTS Program contributes evidence to bridge this gap by examining the experiences not only of producers who participated in a FTS program but also of those who ceased participation or who chose not to participate. Employing a phronetic approach to social science, this explanatory, sequential, mixed-methods case study obtained quantitative and textual data from a mail survey, as well as data from two stints of qualitative fieldwork, in fall 2011 and fall 2012, which involved semistructured interviews and participant observation. Archival research completed the study methods used to gain a deeper understanding of farmers’ perspectives, practices, values, and experiences that informed their decisions to participate or not in a top-down-administered FTS program. Data collection was driven by the concept of farmers’ engagement. As such, eight categories of farmers’ engagement with the Oklahoma Farm to School Program emerged. This research answers these value-rational questions (Flyvbjerg, 2001): (1) Which farmers gain, and which farmers lose, by which mechanisms of power? (2) Is this desirable? (3) What should be done? Results provide evidence of geographically uneven development of a FTS program and incompatibilities between small- to midscale farming and the structure and governance of federal child-nutrition programs.
Keywords: Farmers' engagement in alternative food networks; Structure and agency through farmers' engagement; Oklahoma Farm to School; Rural geography; Mixed methods; Phronesis